High performance area measurement system for leather industries. (2021) - Tamilselvan, K.S.; Vijayalakshmi, A.; Sumithra, M.G.; Vidhya, B.; Satheesh Kumar, S.; Chandran, V.
Abstract: India is one of the leading producers of leather and leather products. Leather Sheet provided by the Tanners is in irregular shape and one of the main factors of its cost is based on its surface area. To calculate the size of the leather, different methods are used which include manual, mechanical and electronics systems. The presently used systems are offer greater amount of error in the measurement due to its irregular shape and cost of the system also high. The proposed research work is development of a prototype with surface area measurement system based on image processing in which a digital photographic image of leather sheet is placed on a conveyer belt having Variable Frequency Drive controlled rollers. IR sensors are used as feedback mechanism for practical implementation of the system which is used to minimize the error in surface area calculations. The main objective is to develop a flat surface area measuring system which is used to calculate the surface area of any irregular sheet. The irregular leather sheet is used in this work. The system is self-protected by user name and password set through software for security purpose. Only authorized user can enter into the system by entering the valid pin code. After entering into the system, the user can measure the area of any irregular sheet, monitor and control the system. The heart of the system is Microcontroller (Atmega328p) which controls the complete working of the system. The controlling instructions for the system are given through the designed Human to Machine Interface (HMI). For communication purpose the GSM modem is also interfaced with the Arduino Microcontroller. The remote user can also monitor the current status of the devices by sending SMS message to the GSM modem.